Labour issues on constructive dismissal / Mazlina Ahmad Zayadah - Zayadah, Mazlina Ahmad (Universiti Teknologi MARA Cawangan Pahang, 2005)
Constructive dismissal is unlike any other form of termination in that the employer takes the initiative by leaving his employment and yet, a dismissal is considered to have taken place. How is this possible? The industrial law recognizes the right of an employee to walk off the job when the actions and behaviours of the employer are so unacceptable and unreasonable that they amount to a breach of contract. This paper will discuss labour issues on constructive dismissal especially on the differences between constructive dismissal and unfair dismissal; circumstances that may give rise to a claim for constructive dismissal; and procedures on how to deal with the constructive dismissal issues.